Incidence and risk factors of depressive symptoms in 4 years of follow-up among mid-aged and elderly community-dwelling Chinese adults: findings from the China Health and Retirement Longitudinal Study - Jing Liao; Yue Wen; Chunjuan Liu; Yiqiong Yin; Dongmei Wu (BMJ Open, 2019)
Objectives The purpose of this study was to examine the incidence of depressive symptoms, and determine if baseline risk factors conferred a risk for incident depressive symptoms in nationally representative sample of mid-aged and elderly Chinese adults.Design This study was a secondary analysis of a prospective cohort from a nationally representative sample.Setting Community samples were recruited from the baseline survey of the China Health and Retirement Longitudinal Study. A four-stage, stratified, cluster probability sampling strategy was used, which included 10 257 households with members aged 45 years or older and their spouse.Participants A total of 11 533 participants free of depressive symptoms at baseline were identified, and 10 288 were re-examined in either the first and/or the second follow-up surveys. The current analysis was conducted among the 10 288 participants.Primary and secondary outcome measures Depressive symptoms were measured by the Center for Epidemiological Studies Depression Scale short form.Results The findings showed that the incidence of depressive symptoms in a 4-year follow-up was as high as 22.3%. The incidence was much higher in rural areas (25.7%) and in women (27.9%). Furthermore, participants with 1 hour longer of night-time sleep had a 10% lower risk of developing depressive symptoms. Compared with individuals who perceived their health status as poor, those who perceived their health status as excellent had a 62% lower risk of developing depressive symptoms. In addition, having diabetes (OR=1.19), chronic kidney disease (OR=1.32), chronic digestive disorders (OR=1.15) and arthritis (OR=1.43) at baseline increased the risk of depressive symptoms. However, baseline body mass index was not associated with the subsequent depressive symptoms in this population.Conclusions This study highlights the importance of developing an appropriate screening test to identify depressive symptoms for those who are vulnerable and ensure these individuals can receive early interventions for depressive symptoms.